Localization of myoglobin in mitochondria: implication in regulation of mitochondrial respiration in rat skeletal muscle. Issue 5 (2nd March 2021) - Koma, Rikuhide; Shibaguchi, Tsubasa; Pérez López, Claudia; Oka, Toshihiko; Jue, Thomas; Takakura, Hisashi; Masuda, Kazumi
Abstract: Mitochondria play a principal role in metabolism, and mitochondrial respiration is an important process for producing adenosine triphosphate. Recently, we showed the possibility that the muscle‐specific protein myoglobin (Mb) interacts with mitochondrial complex IV to augment the respiration capacity in skeletal muscles. However, the precise mechanism for the Mb‐mediated upregulation remains under debate. The aim of this study was to ascertain whether Mb is truly integrated into the mitochondria of skeletal muscle and to investigate the submitochondrial localization. Isolated mitochondria from rat gastrocnemius muscle were subjected to different proteinase K (PK) concentrations to digest proteins interacting with the outer membrane. Western blotting analysis revealed that the PK digested translocase of outer mitochondrial membrane 20 (Tom20), and the immunoreactivity of Tom20 decreased with the amount of PK used. However, the immunoreactivity of Mb with PK treatment was better preserved, indicating that Mb is integrated into the mitochondria of skeletal muscle. The mitochondrial protease protection assay experiments suggested that Mb localizes within the mitochondria in the inner membrane from the intermembrane space side. These results strongly suggest that Mb inside muscle mitochondria could be implicated in the regulation of mitochondrial respiration via complex IV. Abstract : Recently, we showed the possibility that the muscle‐specific protein myoglobin (Mb) interacts with mitochondrial complex IV to augment the respiration capacity in skeletal muscles. However, the precise mechanism for the Mb‐mediated upregulation remains under debate. Our mitochondrial protease protection assay experiments revealed that Mb localizes within the mitochondria in the inner membrane from the intermembrane space side, strongly suggesting that Mb inside muscle mitochondria could be regulating mitochondrial respiration via complex IV.